Impact of Endoscopic Thoracic Sympathectomy among Hyperhidrosis Patients at A Tertiary Care Center: Endoscopic Thoracic Sympathectomy among Hyperhidrosis Patients - Khan, Muhammad Abid; Khan, Faridullah; Aslam, Tahir (Pakistan Journal of Health Sciences, 2025)
Hyperhidrosis is characteristically termed as excessive sweating excessively even during normal situations. Objectives: To assess the dynamics of sweating in patients with hyperhidrosis before and after treatment with Endoscopic Sympathectomy (ETS). Methods: This pre-post intervention research was carried out at the Thoracic Surgery Unit of Lady Reading Hospital, Peshawar, from January 2023 to December 2024. Patients presenting with sweating of either gender, between 18 to 60 years of age, diagnosed with primary hyperhidrosis, were included in the study. Patients having secondary hyperhidrosis, female with symptoms of menopause, patients having generalized sweating, with severe or multiple co-morbidities such as pulmonary or cardiac issues, chronic illness (uncontrolled) or with any neurological condition were excluded from the study. SPSS version 23.0 was used for data analysis. Paired Student t-test was applied for sweating parameters before and after ETS, keeping p<0.05 statistically significant. Results: The study included 53 patients with a mean age of (34.55 ± 8.72) years, nearly equally distributed by gender. Axillary hyperhidrosis was the most common type (43.4%), and most patients had HDSS grades 3or 4. Post-ETS, all sweat parameters showed significant improvement. Notably, BSR reduced to 0.09 ± 0.07 mg/min/cm², PSR to 0.2 ± 0.17 mg/min/cm², SV to 0.07 ± 0.05 mg/cm², and ST to (12.28 ± 10.8) seconds. These findings demonstrate that ETS effectively reduces the severity and extent of sweating in patients with hyperhidrosis. Conclusions: A significant reduction in sweating parameters of patients with hyperhidrosis undergoing Endoscopic Thoracic Sympathectomy.